Success Factors for Construction Waste Recycling in Developing Countries: A Project Management Perspective - Abdul Rahimi, Abdul Rahman; Badraddin, A. K.; Muzamir, Hasan; Nor’Aini, Yusof (Springer, 2021)
Construction industries around the world are generating a large number of wastes that end at landfills every year, and recycling is one of the approaches for minimizing that amount. While various strategies have been adopted in practice, recycling rates of construction projects are still at a low level in numerous countries. Therefore, identifying factors that influence the successful recycling of construction waste is crucial. This study identifies the success factors for recycling construction waste from industry practitioners’ perspectives. To achieve this objective, interview data with project managers are analyzed using the thematic analysis. The major findings from the analysis are: (1) the success factors relate to both people or process; (2) people-related factors involve having individuals that are highly competent, aware on construction waste recycling, and knowledgeable; (3) process-related factors include having a detailed project planning, adequate education and training programs, clear project scope and design, effective procurement system, and consistent monitoring of the construction waste recycling system; and (4) the criticality of the success factors differs between developing countries. This research adds to the body of knowledge by providing a set of success factors for recycling construction waste, which can assist researchers and practitioners in developing strategies to increase recycling rates of construction projects.